2018
DOI: 10.1021/acs.jpcc.7b09832
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Unusual Redox Cycle at the Vanadia Ceria Interface

Abstract: This work investigates the effect of changing the vanadia/support interface on the redox properties of the material for the oxidative dehydrogenation reaction of small alkanes. In particular, ternary V2O5/CeO2/SiO2 catalysts are compared to vanadia on ceria and CeVO4 catalysts. Modifications in the CeO2 phase by the effect of the silica support and the creation of new V–Ce–Si interfaces induce substantial changes in the phases and behavior of vanadium species as well as CeO2, thus modifying the reaction mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…In the case of ceria-zirconia supports, polyvanadates were shown to interact preferentially with the CeO 2 portion of the mixed oxides and to form CeVO 4 at high temperature [122]. Operando studies during oxidative dehydrogenation of ethane suggested that the V-O-Ce bonds must be the sites involved in the rate-determining step [123,124]. Finally, the vanadia structures on different nanoshaped ceria were identified by in situ visible (633 nm) and UV (325 nm)…”
Section: Vanadium Oxide Supported On Ceomentioning
confidence: 99%
“…In the case of ceria-zirconia supports, polyvanadates were shown to interact preferentially with the CeO 2 portion of the mixed oxides and to form CeVO 4 at high temperature [122]. Operando studies during oxidative dehydrogenation of ethane suggested that the V-O-Ce bonds must be the sites involved in the rate-determining step [123,124]. Finally, the vanadia structures on different nanoshaped ceria were identified by in situ visible (633 nm) and UV (325 nm)…”
Section: Vanadium Oxide Supported On Ceomentioning
confidence: 99%
“…Another important factor to be considered in combination with speciation‐driven reactivity is the dynamic behavior of the active sites under reducing and oxidizing environments. Operando XANES/EXAFS studies allowed the identification of differences in vanadium site dynamics during redox cycles in V‐based mixed oxides and binary V 2 O 5 /CeO 2 and ternary V 2 O 5 /CeO 2 /SiO 2 systems . Recently, Ek et al .…”
Section: Introductionmentioning
confidence: 99%
“…Operando XANES/EXAFS studies allowed the identification of differences in vanadium site dynamics during redox cycles in Vbased mixed oxides [27] and binary V 2 O 5 /CeO 2 and ternary V 2 O 5 / CeO 2 /SiO 2 systems. [28] Recently, Ek et al [29] explored the facetdependent reactivity of VO x species on TiO 2 previously observed in the selective reduction of NO to NH 3 [30] by visualizing redox dynamic processes over (001) and (101) facets of the oxide applying combined atomic-resolution TEM and electron energy loss spectroscopy (EELS) under alternated oxidizing and reducing environments. By applying in situ spectroscopic [31][32][33] and atomic-resolution imaging [34][35][36] techniques to monitor redox properties under a reaction environment, new ways are opened to move towards a more complete understanding of the reactivity in oxide-catalyzed processes.…”
Section: Introductionmentioning
confidence: 99%
“…Bañares and coworkers for a ternary VOx/CeO2/SiO2 system. 17 The activity in selectively oxidizing methanol to formaldehyde at ceria-supported vanadia catalysts depends on the amount of vanadium deposited on the surface. 9,[18][19] To understand this behavior at the atomic level, model studies are indispensable.…”
Section: Introductionmentioning
confidence: 99%